The Building Wealth and Health Network: methods and baseline characteristics from a randomized controlled trial for families with young children participating in temporary assistance for needy families (TANF). (December 2016) - Sun, Jing; Patel, Falguni; Kirzner, Rachel; Newton-Famous, Nijah; Owens, Constance; Welles, Seth; Chilton, Mariana
Abstract Background Families with children under age six participating in the Temporary Assistance for Needy Families Program (TANF) must participate in work-related activities for 20 h per week. However, due to financial hardship, poor health, and exposure to violence and adversity, families may experience great difficulty in reaching self-sufficiency. The purpose of this report is to describe study design and baseline findings of a trauma-informed financial empowerment and peer support intervention meant to mitigate these hardships. Methods We conducted a randomized controlled trial of a 28-week intervention called Building Wealth and Health Network to improve financial security and maternal and child health among caregivers participating in TANF. Participants, recruited from County Assistance offices in Philadelphia, PA, were randomized into two intervention groups (partial and full) and one control group. Participants completed questionnaires at baseline to assess career readiness, economic hardship, health and wellbeing, exposure to adversity and violence, and interaction with criminal justice systems. Results Baseline characteristics demonstrate that among 103 participants, there were no significant differences by group. Mean age of participants was 25 years, and youngest child was 30 months. The majority of participants were women (94.2 %), never married (83.5 %), unemployed (94.2 %), and without a bank account (66.0 %). Many reported economic hardship (32.0 % very low household food secure, 65.0 % housing insecure, and 31.1 % severe energy insecure), and depression (57.3 %). Exposure to adversity was prevalent, where 38.8 % reported four or more Adverse Childhood Experiences including abuse, neglect and household dysfunction. In terms of community violence, 64.7 % saw a seriously wounded person after an incident of violence, and 27.2 % had seen someone killed. Finally, 14.6 % spent time in an adult correctional institution, and 48.5 % of the fathers of the youngest child spent time in prison. Conclusions Baseline findings demonstrate that caregivers participating in TANF have suffered significant childhood adversity, adult violence exposure, and poverty-related stressors that can limit workforce success. High prevalence of housing and food insecurity, exposure to adversity, violence and criminal justice systems demands comprehensive programming to support families. Trauma-informed approaches to career readiness such as the Building Wealth and Health Network offer opportunities for potential success in the workforce. Trial registration This study is retrospectively registered with ClinicalTrials.gov The Identifier is:NCT02577705 The Registration date is October 13, 2015